Wellness and Drivers of Burnout. (July 2020) - Talwalkar, Vishwas R.; Weiss, Jennifer
Abstract : Introduction: Promoting physician wellness in the current environment of increasing burnout presents a great challenge to the Pediatric Orthopaedic Society and its members. Pediatric Orthopaedic Society of North America (POSNA) has been a leader in recognizing this problem and organizing to combat it. The increasing rates of job dissatisfaction, burnout, depression, and suicide demand comprehensive and focused action to identify and address the drivers of burnout. Continuing to ignore this problem endangers our organization, our members, our families, and our patients. Methods: A review of relevant literature and the work of the POSNA wellness committee was completed. Results: Addressing the epidemic of burnout requires a sustained effort to address intrinsic factors such as health, performance, and resilience as well as external factors that affect practice efficiency and environment. Discussion and Conclusions: The goal of this effort is restoration of joy to the practitioners in medicine and more compassionate care for the patients who seek it.